Study on the crack propagation morphology and initiation law of coal rock under the action of underwater electric pulse - XianKai Bao; Bin Jiang; GuangQin Cui; XiaoFan Zhang; Tong Zhang; Wu Zhang (Scientific Reports)
Abstract Based on the symmetric initiation mechanism of double-wing cracks in coal rock mass induced by high-pressure electro-recoil water pressure, fracturing experiments have been performed on coal rock mass under different water pressures and discharge conditions using high-voltage electric pulse hydraulic fracturing devices. Combined with CT scans, the crack spatial distribution inside the post-break coal rock mass was analyzed and found that the edge of the water injection hole is prone to produce double-wing cracks along the drilling hole diameter. ABAQUS is used to verify the physical test and extend the test conditions, the geometric parameter change, morphological expansion rule and crack initiation mechanism of double-wing crack in coal rock mass under different discharge conditions and ground stress conditions are studied. The results show that the cracks around the borehole of coal rock mass crack symmetrically under the action of high-voltage electric pulse in water. When the impact load of the high-voltage electric pulse is small(3 MPa hydrostatic pressure, 7 kV discharge voltage), cracks crack symmetrically around the drilling hole, and when the impact load is large(3 MPa hydrostatic pressure, 13 kV discharge voltage), most of the cracks inside the specimen crack symmetrically along the radial or tangential wings of the drilling hole, and the cracks change from multiple pairs of double-wing cracks to a pair of double-wing cracks with the weakening of the shock wave energy until only one single wing crack remains. With the increase of discharge voltage, the length, width, area and complexity of the cracks in both wings will increase in different degrees. With the increase of in-situ stress difference, the crack is more inclined to the direction of the maximum principal stress and eventually expands along the direction of the maximum principal stress. The results further shed light on the initiation and propagation laws of double-wing crack during high-voltage electrical pulse fracturing of coal rock in water and provide theoretical support for efficient extraction of coalbed methane from high-voltage electrical pulse fracturing of coal rock mass in water in China.